Schisandrin B downregulates exosomal fibronectin 1 expression to inhibit hepatocellular carcinoma growth - Baoyi Jiang; Jie Yang; Qingtian Huang; Qingtian Huang; Wei Li; Qian Peng; Huoye Gan; Tieli Peng; Leyi Yao; Ling Qi; Ling Qi (Frontiers in Pharmacology)
IntroductionIn recent years, natural compounds have attracted wide attention for the treatment of liver cancer due to their therapeutic potential and reduced toxicity. Among these, Schisandrin B (Sch B), a primary bioactive component derived from Schisandra chinensis, has shown notable antitumor activity; however, its specific mechanism remains unclear.MethodsThe effect of Sch B on the growth of hepatocellular carcinoma(HCC) cells were assessed using CCK-8 assay, colony formation assay and EdU assay, and apoptosis was detected by flow cytometry. The co-culture system of macrophages and HCC cells was established to detect the effect of Sch B on the cell viability and cell cycle changes of HCC cells in the co-culture system. Then, the migration of HCC cells in the co-culture system was studied using a subtoxic concentration of Sch B. Exosomes of the co-culture system with or without Sch B effect were collected for identification and protein spectrum analysis. The differential protein was analyzed by KEGG enrichment analysis and protein interaction network, which was verified by western blotting. Meanwhile, the expression changes of macrophage polarization markers were detected. Finally, the inhibitory effect of Sch B on HCC and the changes of FN1 were verified by in vivo experiments.ResultsSch B inhibited HCC cell growth; moreover, it significantly suppressed HCC cell proliferation in the co-culture system and induced S-phase cell cycle arrest by downregulating CDK4, CDK2, and cyclin A2 while upregulating p27 Kip1. Additionally, Sch B inhibited the migration of HCC cells in the co-culture system.The differentially expressed protein fibronectin 1(FN1) in liver cancer patients was higher than that in healthy people. Moreover, after SchB treatment, the expression of FN1 protein in exosomes decreased and the macrophages exhibited M1 polarization. In vivo experiments also verified that Sch B inhibited HCC growth and downregulated the expression of FN1 protein in tumor tissues.ConclusionSch B may inhibit the development of HCC by inhibiting the expression of exosomal FN1during interactions between macrophages and HCC cells.